solve by completing the square. 2 x 2 + 2 x − 3 = 0

suchonosdy

suchonosdy

Answered

2022-07-26

solve by completing the square.
2 x 2 + 2 x 3 = 0

Answer & Explanation

cindysnifflesuz

cindysnifflesuz

Expert

2022-07-27Added 19 answers

2 x 2 + 2 x 3 = 0
Divide through bywhatever is multiplied on the squared term.
x 2 + x 3 2 = 0
Take half of thecoefficient (don't forget the sign!) of the x-term, and square it. Add thissquare to both sides of the equation.
x 2 + x 3 2 + .25 = .25
Bring the 3/2 over toother side
x 2 + x + .25 = 3 2 + .25
( x + 5 ) 2 = 1.75
square root both sides
x ± .5 = 1.75
x = 1.75 ± .5
x = 7 4 ± 1 2
and this can be rewrote:
x = 7 2 ± 1 2
x = 1 ± 7 2
Alonzo Odom

Alonzo Odom

Expert

2022-07-28Added 4 answers

I would use the quadratic formula which is: ( b ± b 2 4 a c ) / 2 a
Using that:
( 2 ± 22 4 ( 2 ) ( 3 ) ) / 2 ( 2 ) = ( 2 ± 28 ) / 4

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?